Uranium in alkaline rocks - Murphy, M.; Wollenberg, H.; Strisower, B.; Bowman, H.; Flexser, S.; Carmichael, I. (Lawrence Berkeley Laboratory, 1978)
Geologic and geochemical criteria were developed for the occurrence of economic uranium deposits in alkaline igneous rocks. A literature search, a limited chemical analytical program, and visits to three prominent alkaline-rock localities (Ilimaussaq, Greenland; Pocos de Caldas, Brazil; and Powderhorn, Colorado) were made to establish criteria to determine if a site had some uranium resource potential. From the literature, four alkaline-intrusive occurrences of differing character were identified as type-localities for uranium mineralization, and the important aspects of these localities were described. These characteristics were used to categorize and evaluate U.S. occurrences. The literature search disclosed 69 U.S. sites, encompassing nepheline syenite, alkaline granite, and carbonatite. It was possible to compare two-thirds of these sites to the type localities. A ranking system identified ten of the sites as most likely to have uranium resource potential.